AN EXPERIMENTAL INVESTIGATION OF BOND AND COMPRESSIVE STRENGTH OF CONCRETE WITH MINERAL ADMIXTURES AT HIGH TEMPERATURES - Tanyildizi, Harun; Coskun, Ahmet; Somunkiran, Ilyas (King Fahd Univ Petroleum Minerals, 2008)
[Abstract Not Available]
Keywords: Elevated-Temperatures; Performance